A influência da variabilidade da precipitação na distribuição dos casos de leptospirose em Minas Gerais entre 1998-2012 - Flavia Regina Lacerda Suassuna Dutra (2016)
This work is anchored in Meteorology, Physical Geography and Epidemiology and was developed in stages that culminated in three articles, with specific objectives: (i) Article I - consisted of analysis of the most important aspects of descriptive epidemiology of leptospirosis and the timeline distribution form of the disease and its connexion with precipitation in Minas Gerais during the rainy months of Dec-Jan-Feb between 1998-2012; (ii) Article II - statistical approach applied to SACZ-ENSO associations that occurred in DJF. A behavioral analysis of both phenomena and their impact was made on positive anomalies (+) of rainfall that affected the total cases higher for 2002-2012; (iii) Article III - climatological analysis and dynamics of atmospheric variables that are important in maintaining SACZ and that caused the anomalies (+) of rainfall, which in turn favored the increase of cases in the state. Health data were obtained from DATASUS and atmospheric and oceanic variables are provided by CPTEC and CPC / NOAA. Analysis and more relevant results: 1 - counties with the largest populations the disease appeared endemic with seasonal epidemic fluctuations, in smaller municipalities the predominant occurrence was through outbreaks, with cases concentration in a few years with high incidence rates in rainy periods. The higher frequencies of the disease according to the meso/municipalities were located in NE-SW orientation, including part of central, eastern and southern Minas Gerais state. 2 - the highest frequency SACZ occurred in Dec-Jan (30 episodes / month), high frequency events (7 episodes / quarter) occurred in the summers of: 2006/2007, 2007/2008, 2010/2011, 2011/2012 and the average frequency (5-6 episodes) in: 2002/2003 (5), 2003/2004 (5), 2005-2006 (6), 2008-2009 (6), 2009-2010, (5) number of episodes in parentheses. The time series of SST anomalies in the tropical Pacific region and the SACZ showed significantly correlated with "lag" of 1-2 months between sets. The correlation of the Atlantic SACZ was negative (-), ie; anomalously cold water are associated with the increase precipitation. 3 - in El Niño years, the SACZ is positioned further south of Minas Gerais, where it is observed more moisture flow of air and heat contrast on the southeastern sector of MG, favoring the heat convection that would generate local instabilities. In this situation, the relief region would have a significant contribution, since the topography favor the local circulation, which in turn, associate to the instabilities of SACZ, possibly contributing to generate and provide feedback mesoscale systems, causing precipitation abnormalities (+) and thus favoring the increase of disease cases in this sector. In La Niña years, the heat contrast region moves more to the state center and SACZ stands more continental, causing intense convective activity in the largely state area favoring the occurrence of floods, especially in located mesoregions in southeastern of Minas Gerais, justifying the number increase of disease cases observed in this sector in La Niña years.